Induced Breeding in Clarias gariepinus: A Systematic Review and Meta-Analysis of Overprim and It’s Saline Dilution Doses - Reuben, Laraba Love; Michael, Oshimagye Ibagye; Stephen, Mathew (Darul Yasin Al Sys, 2025)
This review is on the effects of Ovaprim, a synthetic hormone and its dilutions used for inducing spawning and breeding, on the reproductive performance of Clarias gariepinus. By obtaining data from multiple studies, this research assessed key reproductive measures, including fertilization rates, hatchability, and survival rates, in relation to varying concentrations of Ovaprim and saline dilutions. Through a meta-analysis approach, the study findings revealed that the administration of Ovaprim, particularly at a 1:10 saline dilution, significantly enhances fertilization and hatchability rates compared to control groups. However, the relationship between these metrics and survival rates is diverse, with survival not consistently correlating with improvements in fertilization and hatchability. The variability observed across studies highlights the influence of diverse environmental and biological factors on reproductive success.